Computational models of emotion, personality, and social relationships for interactions in games - Chowanda, Andry; Blanchfield, Peter; Flintham, Martin; Valstar, Michel (International Foundation for Autonomous Agents and Multiagent Systems, 2016)
We present a novel computational model of emotion, personality and social relationships, implemented and evaluated in an existing commercial game (The Elder Scrolls V: Skyrim). We argue that Non Player Characters (NPCs) with such capabilities will accommodate a new experience in playing games and provide evidence supporting this. Applying the ERiSA Framework [1, 2] to the Skyrim Creation Kit, we designed a simple quest and 2 unique NPCs to interact with. When the ERiSA framework is used, players reported significant changes in their social relationship with the two NPCs compared to the baseline. Most importantly, the results further indicate that the models provide a new experience in playing games. In particular, players report enhanced emotional attachment to the NPCs and appear to forge relationships with the NPCs. Finally, the implemented models result in significant changes in the game engagement and the game immersion score.